Maternal effect determines drought resistance of eggs in the predatory mite Phytoseiulus persimilis - Le Hesran, Sophie (Oecologia, 2019)
The ability of an organism to adapt to short-term environmental changes within its lifetime is of fundamental importance. This adaptation may occur through phenotypic plasticity. Insects and mites, in particular, are sensitive to changes in temperature and humidity, especially during the juvenile stages. We studied the role of phenotypic plasticity in the adaptation of eggs to different relative humidity conditions, in the predatory mite Phytoseiulus persimilis, used worldwide as a biological control agent of the spider mite Tetranychus urticae. The biocontrol efficacy of P. persimilis decreases under dry conditions, partly because P. persimilis eggs are sensitive to drought. We exposed P. persimilis adult females from two different strains to constant and variable humidity regimes and evaluated the hatching rate of their eggs in dry conditions, as well as the survival and oviposition rates of these females. Whereas the eggs laid by P. persimilis females exposed to constant high humidity did not survive in dry conditions, females exposed to constant low humidity started laying drought-resistant eggs after 24 h of exposure. Survival and oviposition rates of the females were affected by humidity: females laid fewer eggs under constant low humidity and had a shorter lifespan under constant high and constant low humidity. The humidity regimes tested had similar effects across the two P. persimilis strains. Our results demonstrate that transgenerational phenotypic plasticity, called maternal effect, allows P. persimilis females to prepare their offspring for dry conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00442-019-04556-0) contains supplementary material, which is available to authorized users.